Colloidal interactions between model foulants and engineered surfaces: Interplay between roughness and surface energy - Thomas Horseman; Zhangxin Wang; Shihong Lin (Chemical Engineering Journal Advances, 2021)
Fouling on submerged surfaces is a major limiting factor for membranes, heat exchangers, and marine vessels as it induces mass and heat transfer resistances that increase operating costs and lead to system failures. While the role of surface roughness on fouling has been extensively studied, the specific effect of surface roughness on fouling is debated in literature. In this study, we employed force spectroscopy based on atomic force microscopy with two model colloidal probes to elucidate the role of surface roughness on foulant-surface interactions. Specifically, we quantified the strength and characteristic lengths of the interactions between the colloidal probes and hydrophilic and hydrophobic surfaces with and without surface texture. We found that hydrophilic surfaces are generally less prone to foulant adhesion than hydrophobic surfaces and that increasing roughness of a hydrophilic surface mitigates foulant adhesion. In comparison, we found that increased roughness of a hydrophobic surface increases the attractive foulant-surface interaction, and thus, its fouling propensity. Based on the results from this study, the implications for developing surfaces with fouling resistance are also examined.